La régulation des marchés aux animaux (wetmarkets) en Chine durant la crise de Covid-19 - Frédéric Keck; Nan Nan (Métropoles)
While the health crises of the last twenty years have highlighted China's wet markets as potential transmission sites for zoonotic pathogens such as influenza viruses or SARS coronaviruses, Chinese consumers have maintained a demand for freshness and proximity that drives them to these markets rather than to supermarkets. Based on a literature review and a survey in the city of Chengdu, this article shows the differentiation of forms of wet market (retail or wholesale) and slaughtering practices according to the rural areas in which they are located. It highlights the fact that the control of zoonotic risks in these markets takes place more generally in a context of privatisation and transformation of relations between town and country, which delegates the responsibility of control to merchants and increases the uncertainty of sellers about the possibility of selling their animals on a regular basis.